2014
DOI: 10.1007/s12032-014-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of serum hepatocyte growth factor levels in patients undergoing primary radiotherapy for glioma: effect on progression-free survival

Abstract: Hepatocyte growth factor (HGF) has been shown to be overexpressed in gliomas, and high-grade gliomas (glioblastoma multiforme) express more HGF than lower-grade astrocytoma, and HGF enhances their resistance to radiotherapy. To examine the effect of serum HGF levels on the likelihood of response to radiotherapy and the disease-free survival in patients with glioma, the blood samples of the patients were collected before commencing treatment and serum HGF was measured by quantitative ELISA in 48 patients with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Several studies have documented that HGF is overexpressed in gliomas, and high-grade gliomas express more HGF than lower-grade astrocytomas. Serum HGF influenced progression-free survival [16]. SiBMK1/U87 cells showed dramatically decreased invasive ability compared with SCR/U87 cells (Fig.…”
Section: Bmk1 Promoted Glioma Cell Invasionmentioning
confidence: 96%
“…Several studies have documented that HGF is overexpressed in gliomas, and high-grade gliomas express more HGF than lower-grade astrocytomas. Serum HGF influenced progression-free survival [16]. SiBMK1/U87 cells showed dramatically decreased invasive ability compared with SCR/U87 cells (Fig.…”
Section: Bmk1 Promoted Glioma Cell Invasionmentioning
confidence: 96%
“…HGF inhibition is as effective as standard chemotherapy in inhibiting local tumor growth [45]. The fact that the concentration of these factors is high in the peripheral region of glioblastoma multiform, which is a strong brain tumor with advanced invasion skills, supports the view that they play a role in motility [46].…”
Section: Ecm's Invasion and The Stages Of Invasionmentioning
confidence: 98%
“…Activation of the HGF/c-MET pathway has been evaluated using serum or plasma HGF, because HGF is expelled from tumor cells to the extracellular matrix and blood plasma by a paracrine mechanism [ 12 ]. Increased serum HGF (sHGF) has been reported to be a negative prognostic marker in various malignancies including colorectal cancer, gastric cancer [ 13 15 ], prostate cancer [ 16 ], ovarian cancer [ 17 ], breast cancer [ 18 , 19 ], glioma[ 20 ], melanoma [ 21 ], and multiple myeloma [ 22 , 23 ]. Recently, a Spanish group reported that high sHGF in patients with SCLC predicts poor outcome and epithelial-mesenchymal transition (EMT) change in the tumor [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%